Self-care behaviors among type 2 diabetes mellitus patients at Hospital Universiti Sains Malaysia - Fauzan, Ahmadulhadi (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2013)
The purpose of this cross-sectional study is to determine the self care behaviours among type II diabetes mellitus who attend to Klinik Rawatan Keluarga in Hospital USM. The respondents of 45patients of type II diabetes mellitus were studied. The Diabetes Health Beliefs Patients adopted from the Health Beliefs Model was used as the theoretical framework of the study. A self-administered questionnaires used in this study was demographic data and level of self care behaviours questionnaires, which were distributed to the respondent by nonprobability, convenience sampling method. The data was analysed by using Statistical Whitney analysis, significant association were found between selected demographic data (level of education and income) and patient’s self care behaviours. From this study, score of self-care behaviors among type II diabetes mellitus patients at Hospital USM were at moderate level. 95.56 % from 45 respondents have score from 24-37,which was at moderate good self care behaviors. The mean score and standard deviation of 10 items in Self Care Behaviour is 28.17 and 3.79 respectively, ranging from 20 to 36 marks. Malaysian living with diabetes cope everyday with suffers from the disease and fears of complication secondary to diabetes, resulting in rates of blindness, renal disease and lower limb amputations. Understanding how they cope with diabetes is important. Although studies have been done on self care behaviours in developed countries, little is known about self-care behaviours among type II diabetes mellitus patient in Hospital Universiti Sains Malaysia.